Identification of some Benin Republics Guinea yam (Dioscorea cayenensis/Dioscorea rotundata complex) cultivars using Randomly Amplified Polymorphic DNA - Dansi, A.; Mignouna, H.; Zoundjihékpon, J.; Sangare, A.; Ahoussou, N.; Asiedu, Robert (2000)
DNA from twenty-three late maturing cultivars of Guinea yams (D. cayenensis/D. rotundata complex) from the Benin Republic that could not be separated using isozyme markers, were examined using randomly amplified polymorphic DNA (RAPD) markers with decamer primers of arbitrary sequence. All the twelve primers tested were informative and yielded 63 amplified DNA bands from which 47 (75%) were polymorphic. Although no single primer produced polymorphic bands in all cultivars, the great majority of the cultivars were separated with the combinations of polymorphic bands generated by various primers. Putative duplicates and cultivar misclassifications were identified. Many morphologically distinct cultivars were close. The dwarf cultivar Tam-Sam considered as derived from Tabane, appeared more distant from the latter than was believed. RAPD analysis was found as a practical tool for the identification of duplicates toward establishment of an accurate core collection of Guinea yams in Benin Republic and in the other countries of the African yam belt.